Percepção de alunos e do professor sobre a indisciplina nas aulas de educação física e possibilidades de ação - Custódio, Rafael Henrique (Universidade Federal de São Carlos, 2026)
School indiscipline constitutes a complex and recurring phenomenon in the educational context, presenting direct impacts on pedagogical development, student engagement, and the teaching–learning process, including in Physical Education classes. Considering this issue, the present study aims to describe and correlate the subjective perceptions of students and the teacher regarding variables related to indiscipline in Physical Education classes, based on a problematizing pedagogical intervention, as well as to develop an experience notebook for teaching application. The research was characterized as a qualitative–quantitative investigation of a longitudinal nature, conducted with students from a 4th grade class of Elementary School in a municipal public school in Ibaté, São Paulo, Brazil. As data collection instruments, self-assessment questionnaires answered by students and by the teacher were used, as well as records in field diaries documenting observations throughout ten classes organized based on active methodologies and on student participation in the construction of evaluation criteria and in reflection on students’ behaviors and attitudes. The results showed progressive improvement in variables related to peer relationships, collectivity, care for materials, and learning, indicating greater involvement, cooperation, and self-regulation among students throughout the interventions. A convergence between the evaluations conducted by students and by the teacher was also observed, suggesting an expansion in students’ awareness regarding the elements addressed during the interventions. However, the variable related to parallel conversations showed a small effect, suggesting resistance possibly associated with school culture and with the social perception of Physical Education as a recreational space. Data analysis indicates that pedagogical strategies grounded in active methodologies and in self-assessment as a process of awareness contribute significantly to addressing indiscipline by promoting a sense of belonging and co-responsibility for the educational process. It is concluded that indiscipline should be understood as a multifactorial phenomenon and that participatory pedagogical interventions may favor behavioral changes and improvements in the learning environment, although they require continuity and articulation with the cultural and school context.
Perception of students and the teacher about indiscipline in physical education classes and possibilities for action
Keywords: Educação física escolar; indisciplina; autoavaliação; School Physical Education; indiscipline; self-assessment; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 4. Educação de Qualidade